Forgotten Source: Study M. Laszlo-Kutiuk «Romanian-Ukrainian Literary Relations in XIXth Century the Beginning of XXth Century» (to the Problem of Digitizing Educational Resources) - Yantsos, Nataliia (Didactica Danubiensis, 2022)
The study presents the observations and aesthetic assessment of the leader of the Ukrainian community in Romania in the 20th century, Magdalena Laslzo–Kutsiuk (1928-2010), regarding Ukrainian-Romanian contacts in the 19th and early 20th centuries, which is contained in her course of lectures published on the basis of the Faculty of Slavic Languages of the University of Bucharest (1974). To this day, this work remains unknown to the general public and the Ukrainian reader, as the work was not translated, in particular into Ukrainian. The author analyzes the creativity of the main figures of Romanian culture of the 19th century (G. Asaki, B.P. Hashdeu and others), who touched on the topic of Ukraine in their works, as well as representatives of Ukrainian literature whose works reflected the image of Romania. Depending on the intensity of contacts with the neighboring country, the authors reveal the image of "Ukraine" or the image of the "Romanian people" and everything related to their culture in their work in different ways.